The Line Tender - Allen, Kate, 1977- (New York : Dutton Children's Books, 2019)
Following a tragedy that further alters the course of her life, twelve-year-old Lucy Everhart decides to continue the shark research her marine biologist mother left unfinished when she died years earlier.
Junior Library Guild
Ages 11-14.
Grades 6-9.
710L
A Junior Library Guild selection (JLG)
Keywords: Family life -- Juvenile fiction. -- Massachusetts; Friendship -- Juvenile fiction; Grief -- Juvenile fiction; Loss (Psychology) -- Juvenile fiction; Sharks -- Juvenile fiction; Single-parent families -- Juvenile fiction; Family life -- Fiction. -- Massachusetts; Friendship -- Fiction; Grief -- Fiction; Loss (Psychology) -- Fiction; Sharks -- Fiction; Single-parent families -- Fiction; Family life -- Fiction. -- Massachusetts; Friendship -- Fiction; Grief -- Fiction; Loss (Psychology) -- Fiction; Sharks -- Fiction; Single-parent families -- Fiction; Rockport (Mass.) -- Juvenile fiction; Rockport (Mass.) -- Fiction; Rockport (Mass.) -- Fiction